The Effect of Employability on the Willingness to Work of Vocational Students in West Sumatra - Wirdatun Nisa (Universitas PGRI Yogyakarta, 2026)
The unemployment rate of vocational high school (SMK) graduates in Indonesia, including West Sumatra, remains high despite their work-based education. This suggests a gap between acquired competencies and the willingness to work. This study examines the impact of employability on students’ work motivation. Using a quantitative approach and simple linear regression, data were collected from 200 vocational students via standardized questionnaires. Results show that employability has a positive and significant effect on work volition, with a determination coefficient of 17.2%, while 82.8% of the variation is influenced by other factors. This indicates that strengthening employability, such as technical skills and work readiness, can significantly boost students' motivation to work. The findings underscore the importance of targeted programs, such as career guidance, job skills training, and coaching, in enhancing students' employability from an early stage. Improving these aspects can increase their willingness to enter the workforce and reduce youth unemployment. Keywords: employability, work volition, vocational students